To assess the role of multisite instillation of bupivacaine-xylocaine combination for reducing post-operative pain after elective laparoscopic cholecystectomy - Gandhi, Jignesh A.; Shinde, Pravin H.; Patil, Pratik D.; Thakkar, Samarth A.; Digarse, Rohan D. (International Journal of Research in Medical Sciences, 2016)
Background: Pain following laparoscopic surgery is multifactorial, arising from trocar sites (somatic pain), operative site (visceral pain) and shoulder pain (referred from diaphragmatic irritation because of pneumo-peritoneum). Currently no standard of care exists to reduce post-operative pain by use of local analgesia in laparoscopic cholecystectomy. Despite many studies, there are contradictory results. Aim of the study was to assess whether instillation of local anaesthetics at trocar sites and intraperitoneally, reduces the amount of pain experienced in the immediate postoperative period after laparoscopic cholecystectomy. Methods: This prospective study was carried out in the Department of General Surgery in a tertiary medical Centre in Mumbai. 75 subjects were randomized into 2 groups. Group A consisting of 38 patients were subjected to multisite instillation of LA combination (bupivacaine+xylocaine) at trocar site, gall bladder fossa, sub diaphragmatic space. Group B, (control group) consisting of 37 patients was given no such LA. Post operatively, pain was assessed by VAS scale (0-100) at 1,4,24 hours. Both the groups were compared and analysed. Results: Group A showed significantly reduced pain scores at 1, 4 and 24 hours post operatively as compared to group B. Conclusions: Our results indicate that multisite infiltration of local anesthetic combination (bupivacaine+xylocaine) after laparoscopic cholecystectomy surgery significantly reduces pain at 1, 4 and 24 hours postoperatively.